Comparative Evaluation of Efficacy Of 0.2% Chlorhexidine And 0.12% Chlorhexidine and An Herbal Mouthwash in Reducing Dental Aerosol as A Preprocedural Mouthwash - Abhisha K, Abhisha K; Syam, Nita; Ahamed, Shabeer; Lakshmy M, Lakshmy M; Devipriya, Devipriya; Shimreen K, Shimreen K (Journal of Neonatal Surgery, 2025)
Aims: The aim of the present study was to assess and compare the efficacy of different pre-procedural mouth rinses in reducing microorganisms in dental aerosols. Settings and Design:This study was conducted with a total of 40 patients from the department of periodontology, who were randomly assigned into four groups of ten patients each. Methods and Material: Each group was administered a specific pre-procedural mouth rinse distilled water,0.2% CHX,0.12% CHX, or an herbal mouthwash.Aerosols generated by an ultrasonic scaler were collected at a distance of 12 inches from the patient’s mouth onto blood agar plates.These plates were incubated at 37 degrees Celsius for 48 hours, after which CFUs were counted. Statistical analysis used:Data was analyzed using the One-way Anova test followed by BONFEERONI TEST Posthoc test. Results:In the present study, 0.2% CHX and 0.12% CHX shows significantly similar amount of reduction in CFUs when used as a preprocedural mouthwash during ultrasonic scaling followed by an herbal mouthwash, respectively. Conclusions:The findings of the current study shows that usage of pre procedural mouthrinse will reduce the amount of bacterial count in aerosols produced during ultrasonic scaling.The lower concentration of 0.12% chlorhexidine not only maintained optimal clinical results but also enhanced patient compliance.